2021
DOI: 10.1039/d1cc00366f
|View full text |Cite
|
Sign up to set email alerts
|

H-Bonding and intramolecular catalysis of proton exchange affect the CEST properties of EuIII complexes with HP-DO3A-like ligands

Abstract: Eu(HP-DO3A) is present in solution as a mixture of two diastereoisomers whose alcoholic groups are the source of the mobile protons for the CEST effect. The exchange is base catalyzed....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In water, the Gd-L1 relaxivity value of 7.1 mM –1 s –1 , measured for 1 mM concentration at 21.5 MHz, 298 K and neutral pH, appears in agreement with the occurrence of an intramolecular catalysis of the prototropic exchange of the coordinated alcoholic group. , The catalysis likely involves the amide proton, as previously shown for similar systems. Here, the catalytic effect appears even more marked, as the contribution of the OH moiety appears evident already at neutral pH values. Of course, the increased τ R , due to the increased MW (with respect to the parent Gd-HPDO3A), is also important.…”
Section: Discussionsupporting
confidence: 75%
“…In water, the Gd-L1 relaxivity value of 7.1 mM –1 s –1 , measured for 1 mM concentration at 21.5 MHz, 298 K and neutral pH, appears in agreement with the occurrence of an intramolecular catalysis of the prototropic exchange of the coordinated alcoholic group. , The catalysis likely involves the amide proton, as previously shown for similar systems. Here, the catalytic effect appears even more marked, as the contribution of the OH moiety appears evident already at neutral pH values. Of course, the increased τ R , due to the increased MW (with respect to the parent Gd-HPDO3A), is also important.…”
Section: Discussionsupporting
confidence: 75%
“…and by nearly 40-fold in Eu-An-HP-DO3A. 30 This demonstrates that formation of an intramolecular H-bonding network with an exchanging -OH proton used for CEST activation can substantially increase the sensitivity of a paraCEST agent. This exciting observation could lead to new designs that bring the sensitivity of small molecule paraCEST agents like those described above into competition with existing Gd-based T 1 agents.…”
Section: Some Recent Chemical Insights May Prove Useful In Amplifying...mentioning
confidence: 89%
“…Can we find ways to amplify the sensitivity of paraCEST agents through prototropic exchange mechanisms? A recent report by Baroni et al 30 may provide some useful insights. In that study, Baroni et al demonstrated that the presence of a basic site (carboxyl or amine, see Figure 6) in proximity to the hydroxyl group of Ln (HP‐DO3A) allows for formation of a H‐bond with the coordinated ‐OH group that provides a pathway for intramolecular proton exchange and an enhanced CEST signal.…”
Section: Some Recent Chemical Insights May Prove Useful In Amplifying...mentioning
confidence: 94%
See 2 more Smart Citations